2017
DOI: 10.1016/j.jtcvs.2017.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of isolated aortic valve replacement in patients with classic and paradoxical low-flow, low-gradient aortic stenosis

Abstract: AVR can be performed in LFLG AS with low in-hospital mortality. CLFLG AS carries similar in-hospital mortality to PLFLG AS but greater mid-term mortality. Surgery provided excellent functional status among survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…The survival rate in this patient population is low (40-60% at 2 years) with conservative management but 30-day mortality after SAVR is anyway high (8-33%). [19][20][21][22][23][24][25][26][27][28][29][30] In-hospital mortality of our series is 3.4% and comparable with the data reported by Lopez-Marco et al, 31 mortality concerns the classical LF-LG, in comparison with the other groups and these data are consistent with the high mortality rate reported in the literature. Surgery is anyway feasible, as it allows improvement in quality of life.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The survival rate in this patient population is low (40-60% at 2 years) with conservative management but 30-day mortality after SAVR is anyway high (8-33%). [19][20][21][22][23][24][25][26][27][28][29][30] In-hospital mortality of our series is 3.4% and comparable with the data reported by Lopez-Marco et al, 31 mortality concerns the classical LF-LG, in comparison with the other groups and these data are consistent with the high mortality rate reported in the literature. Surgery is anyway feasible, as it allows improvement in quality of life.…”
Section: Discussionsupporting
confidence: 93%
“…The survival rate in this patient population is low (40–60% at 2 years) with conservative management but 30-day mortality after SAVR is anyway high (8–33%) 19–30 . In-hospital mortality of our series is 3.4% and comparable with the data reported by Lopez-Marco et al , 31 whereas 1-year mortality is 5%, lower in comparison with the 14% reported. Higher mortality concerns the classical LF-LG, in comparison with the other groups and these data are consistent with the high mortality rate reported in the literature.…”
Section: Discussionsupporting
confidence: 80%
“…In the study by Clavel et al , compared to cLF-LGAS, patients with pLF-LGAS undergoing AVR were more frequently female and had lower prevalence of comorbidities such as chronic obstructive pulmonary disease (COPD), coronary artery disease (CAD) and chronic kidney disease (CKD) [10]. Lopez-Marco et al documented a higher proportion of females, greater incidence of hypertension and previous neurologic events as well as lower prevalence of diabetes and COPD in patients with pLF-LGAS undergoing AVR as compared to those with cLF-LGAS [11]. In other studies, the comorbidity profile of pLF-LGAS patients did not differ from HGAS patients with comparable age, occurrence of hypertension, diabetes, obesity, CAD and previous MI [9, 12].…”
Section: Discussionmentioning
confidence: 99%